2018
DOI: 10.1007/s10995-018-2638-3
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Food-Based Approaches Alone May Not Ensure Dietary Adequacy for Women and Young Children in South-East Asia

Abstract: Objectives Micronutrient deficiencies, in southeast Asia (SE Asia), remain a public health challenge. We evaluated whether promoting the consumption of locally available nutritious foods, which is a low-risk micronutrient intervention, alone can ensure dietary adequacy, for women of reproductive age and 6-23 m old children. Methods Representative dietary data from Cambodia, Indonesia, Lao PDR, Thailand and Vietnam were analysed using linear programming analysis to identify nutrients that are likely low in pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 36 publications
6
45
0
Order By: Relevance
“…In the context of severe malnutrition, it was shown that no combination of local foods was able to achieve a nutrient density as high as diets promoted by the WHO, thus showing the need for fortified foods in this specific health condition ( 70 ). Several others studies have found that nutritional adequacy was only attainable via the inclusion of fortified products ( 47 , 48 , 69 ). For example, in Kenya, with no zinc-fortified water, only 76% of the zinc RVs could be covered in the nutritionally best diet for young children, which was improved to 101% with the fortified product ( 48 ).…”
Section: Nutritionally Adequate Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of severe malnutrition, it was shown that no combination of local foods was able to achieve a nutrient density as high as diets promoted by the WHO, thus showing the need for fortified foods in this specific health condition ( 70 ). Several others studies have found that nutritional adequacy was only attainable via the inclusion of fortified products ( 47 , 48 , 69 ). For example, in Kenya, with no zinc-fortified water, only 76% of the zinc RVs could be covered in the nutritionally best diet for young children, which was improved to 101% with the fortified product ( 48 ).…”
Section: Nutritionally Adequate Dietsmentioning
confidence: 99%
“…Optifood's modules are further detailed in Supplemental Method s 2 . The Optifood software program has been extensively used for developing FBRs for children aged <2 y [e.g., in Kenya ( 42 , 43 ), Guatemala ( 44 ), Indonesia ( 30 , 45 ), Cambodia ( 46 ), and in 5 Southeast Asian countries ( 47 )], for older children [in specific regions of Malawi ( 39 ) or Kenya ( 48 )], and for women in Guatemala ( 44 ). Diet optimization also contributed to the development of a food guide in Benin for several adult age and sex subpopulations ( 49 ).…”
Section: Nutritionally Adequate Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of growth faltering, indicated by a decline in z‐scores (Victora, de Onis, Hallal, Blössner, & Shrimpton, ) in Cambodia occurs from 6 to 20 months (Dewey & Huffman, ; NIS et al, ). Poor complementary feeding practices are often implicated in the growth faltering observed in low‐ and middle‐income countries (Ferguson et al, ). Borbor (white rice porridge , the traditional weaning food in Cambodia) has inadequate energy and micronutrient nutrient density to sustain adequate growth velocity in the first 2 years of life (Black et al, ; Ferguson et al, ).…”
Section: Background and Rationalementioning
confidence: 99%
“…Poor complementary feeding practices are often implicated in the growth faltering observed in low‐ and middle‐income countries (Ferguson et al, ). Borbor (white rice porridge , the traditional weaning food in Cambodia) has inadequate energy and micronutrient nutrient density to sustain adequate growth velocity in the first 2 years of life (Black et al, ; Ferguson et al, ). Nutrition‐specific interventions aimed at improving complementary feeding seem warranted (Black et al, ; Pham et al, ).…”
Section: Background and Rationalementioning
confidence: 99%